A atuação do secretário executivo como indivíduo-chave nas negociações dos processos decisórios - Carpes, Veridiana Aquino (Universidade do Vale do Rio dos Sinos, 2015)
This work is directed at executive secretarial work and the work of this individual as key in which the main objective was to analyze this professional as an individual key facilitator of decision-making in organizations. We conducted a qualitative study of descriptive, where the population covered by the study was professional performing secretarial functions in medium-sized companies in the Rio Grande do Sul. It was used as data collection instrument a questionnaire composed of 15 questions, with 10 objective questions and 5 essay questions. From the analysis of the results, it was observed that most of the secretarial professionals holds the individual key role in the negotiations, and competence to assist the executive in decision-making. Another factor that was evident is that much of the secretaries have the freedom to express your opinion about some decisions of his head and that maintains a relationship based on trust, feeling able to perform duties and responsibility activities within the company, which characterizes it as an individual key. However, there are still many of those secretaries who do not feel valued by chiefs, performing the job that are sufficiently capable. However, it can be said that the secretary who exercises his profession with ethics and respect can earn the trust of their heads and perform all functions efficiently in order to become active within the company and to grow professionally.
Keywords: Secretariado executivo; Indivíduo-chave; Tomada de decisão; Executive secretariat; Individual key; Decision taking